The relationship between endothelial progenitor cells and pulmonary arterial hypertension in children with congenital heart disease - Hong-Xiao Sun; Guo-Ju Li; Zhan-Hui Du; Zhen Bing; Zhi-Xian Ji; Gang Luo; Si-Lin Pan (BMC, 2019)
Abstract Background Pulmonary arterial hypertension (PAH) caused by congenital heart disease (CHD) is very common in clinics. Some studies have shown that PAH is related to the number of endothelial progenitor cells (EPCs), but there is no report on the relationship between PAH and the number of EPCs in children with CHD. Methods In this study, a total of 173 cases with CHD (from 0 to 6 years old) were collected. According to the mean pulmonary arterial pressure (mPAP) measured by right heart catheterization, these cases were divided into PAH groups (including high PAH group, mPAP> 25 mmHg, n = 32, and the middle PAH group, 20 mmHg ≤ mPAP≤25 mmHg, n = 30) and non-PAH group (mPAP< 20 mmHg, n = 111). Peripheral blood was taken for flow cytometry, and the number of EPCs (CD133+/KDR+ cells) was counted. The number of EPCs /μL of peripheral blood was calculated using the following formula: EPCs /μL = WBC /L × lymphocytes % × EPCs % × 10− 6. Results The median EPCs of the non-PAH group, middle PAH group and high PAH group is 1.86/μL, 1.30 /μL and 0.98/μL, respectively. The mPAP decreases steadily as the level of EPCs increases (P < 0.05). After adjustment of gender, age and BMI, the number of EPCs was significantly associated with a decreased risk of high PAH (OR = 0.37, 95% CI: 0.16-0.87, P < 0.05). However, EPCs was not significantly associated with middle PAH (P > 0.05). Conclusion The findings revealed that the EPCs and high PAH in patients with CHD correlate significantly and EPCs may become an effective treatment for PAH in patients with CHD. EPCs may be a protective factor of high PAH for children with CHD.